Explaining interfirm cooperation and performance: toward a reconciliation of predictions from the resource-based view and organizational economics - Combs, James G.; Ketchen, David J. (Strategic Management Journal, 1999)
Interfirm cooperation and its performance implications are examined in the context of two widely cited theoretical approaches to organizations. Broadly speaking, the resource-based view suggests that firms seek to capitalize on and increase their capabilities and endowments, whereas organizational economics asserts that firms focus on minimizing the costs of organizing. Although these perspectives agree on managers’ likely actions in many areas, their predictions diverge when interfirm cooperation is considered. We take a step toward reconciling these differences by positing that firms place resource-based concerns in front of considerations from organizational economics when deciding whether or not to engage in interfirm cooperation. We examined this prediction using data from 94 publicly held restaurant chains. The results support our integrated view, but also suggest that giving primacy to resource concerns detracts from the performance of some firms. We derive several implications of these findings in an effort to guide subsequent inquiry. Copyright © 1999 John Wiley & Sons, Ltd.